Eurasia’s Maritime Rise and Global Security From the Indian Ocean to Pacific Asia and the Arctic - Gresh, Geoffrey F. (Palgrave Studies in Maritime Politics and Security, 2018)
XXIII, 288 p. 8 illus., 3 illus. in color.